2015
DOI: 10.2341/13-149-l
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sandblasting and Different Primers on Shear Bond Strength Between Yttria-tetragonal Zirconia Polycrystal Ceramic and a Self-adhesive Resin Cement

Abstract: Z-PRIME Plus primer application after air-abrasion presented the best results for improving the bond strength between Y-TZP ceramic and self-adhesive resin cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
90
1
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 18 publications
12
90
1
17
Order By: Relevance
“…This was due to a synergistic effect produced by the increased contact area on the chemical interactions between the 10-methacryloyloxydecyl dihydrogen phosphate (MDP) and carboxylic monomers of the Z-Prime Plus and the monolithic zirconia surface. The reported data of the present study on the effect of the sandblasting and priming agent application on bond strength is in agreement with previous studies 182028…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was due to a synergistic effect produced by the increased contact area on the chemical interactions between the 10-methacryloyloxydecyl dihydrogen phosphate (MDP) and carboxylic monomers of the Z-Prime Plus and the monolithic zirconia surface. The reported data of the present study on the effect of the sandblasting and priming agent application on bond strength is in agreement with previous studies 182028…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion is consistent 192123. Previous studies reported that sandblasting provide higher bond strength than grinding 2328. However, sandblasting caused surface damage and phase transformation (tetragonal to monoclinic) affects the mechanical properties and reliability of zirconia 2329…”
Section: Introductionsupporting
confidence: 83%
“…Since it doesn't contain glass, it cannot be etched by hydrofluoric acid and tribochemical silica coating is not effective 1,2. Therefore, unlike conventional materials, the adhesion with luting cement is weak and the restoration easily falls off 1. Therefore, the tooth surface should be treated with conventional methods, but the inner zirconia surface needs special treatment 1,2,3,4…”
Section: Amentioning
confidence: 99%
“…Therefore, self-adhesive resin cement (SmartCem2, Dentsply, York, PA, USA; Rely X U200, 3M ESPE; BisCem, Bisco Inc.; PermaCem 2.0, DMG, Hamburg, Germany; Multilink Speed, Ivoclar Vivadent, Schaan, Liechtenstein) may be conveniently used for cementation as saving time and reducing errors of multistep processing. The manufacturers do not recommend the use of additional surface treatment on restorations as the self-adhesive resin cement contains functional monomers, but the use of aforementioned primers significantly increase the bond strength 1,2. Zirconia adhesion needs improvement through further research and development.…”
Section: Amentioning
confidence: 99%
“…[20][21][22] As for chemical bonding, many studies reported that using primers and resin cement based on 10-methacryloyloxydecyl dihydrogen phosphate (MDP) monomer increased bond strength. 23,24 They are considered as materials of choice for cementation of indirect alumina and zirconia restorations, since MDP monomer bonded directly to metal oxides and the phosphoric-acid groups of MDP can react with the oxide layer on the zirconia surface. 25,26 It was also shown in previous studies that the creation of a micro-retentive surface is an important factor for achieving strong and durable adhesion, and promotes as well the chemical reaction with MDP monomer.…”
Section: Introductionmentioning
confidence: 99%